2013
DOI: 10.3109/10717544.2013.860502
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and evaluation of gemcitabine-loaded solid lipid nanoparticles

Abstract: Gemcitabine-loaded solid lipid nanoparticles (SLNs) were produced by double emulsification technique using stearic acid as lipid, soy lecithin as surfactant and sodium taurocholate as cosurfactant. Prepared nanoparticles are characterized for particle size and surface morphology using scanning electron microscopy (SEM). Particle yield, entrapment efficiency and zeta potential were also determined. In-vitro release studies were performed in phosphate-buffered saline (PBS) pH 7.4 using metabolic shaker. The form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Diffusion of INZ from lipid matrix also depends on the partitioning of INZ between the lipid phase and the aqueous dissolution media. The same pattern of release was also reported for gemcitabine [29].…”
Section: In Vitro Release Studies and Release Kineticssupporting
confidence: 80%
“…Diffusion of INZ from lipid matrix also depends on the partitioning of INZ between the lipid phase and the aqueous dissolution media. The same pattern of release was also reported for gemcitabine [29].…”
Section: In Vitro Release Studies and Release Kineticssupporting
confidence: 80%
“…The EE of LPNs was higher than that of nanoparticles and common liposomes because the lipid material and the nanoparticle solution were incubated at a certain temperature, and the vesicles exhibited a fusion effect after coming into contact with the nanoparticles and recombining into a continuous bilayer around the nanoparticles, thereby increasing the EE of the LPNs (Figure 2; Table 2). [29][30][31] The preliminary stability evaluation of LNPs was performed by using the influencing factors test according to the guiding principle of the stability test of the preparation, which provided a basis for the subsequent optimization of the preparation process and storage conditions. The results indicated that the LNPs were sensitive to temperature.…”
Section: Results and Discussion Preparation And Characterization Of Tmentioning
confidence: 99%
“…Balb/c mice (4-5 weeks old, weight 25 ± 2 g) were procured from Liaocheng People's Hospital, Liaocheng, China. The pharmacokinetics study was conducted by following the previously reported procedure (Nandini et al 2015) with slight modifications. Four animals each were divided into three groups.…”
Section: Pharmacokinetic Studiesmentioning
confidence: 99%
“…The rapid metabolism and shorter half-life of drug required higher dose and repeated dosing schedule which consequently results in higher toxicity. Thus, it is needed to design a vector which can reduce the burden of frequent dosing and higher toxicity associated with high dosages of GEM (Nandini et al 2015, Sandler et al 2000. Therefore, the novel drug delivery strategies are required to increase the bioavailability of drugs and to reduce side effects.…”
Section: Introductionmentioning
confidence: 99%